Communication as a therapeutic instrument for patients submitted to bone marrow transplantation: a review - Renata Cristina de Campos Pereira Silveira; Ariane Freitas Cardoso; Emília Campos de Carvalho (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2008)
Bone marrow transplantation (BMT) causes psychological effects in patients, especially in terms of autonomy and coping with the situation; therapeutic communication can help patients to recover these. This integrative literature review aims to identify evidence of using communication interventions in patients submitted to BMT. The terms communication and BMT were used to select articles from the following databases:MEDLINE/PubMed, Cinahl and Lilacs. Nine articles were analyzed, distributed between 1991 and 2006, 44% of which came from the United States and 55% were quantitative studies. The results showed the importance of communication among health professionals and patients as a contributing factor to increase commitment in treatment, to facilitate the understanding of the processes involved and to identify their needs, so as to humanize care and formulate strategies to decrease or even put an end to undesirable moment